The application of generosity maxim: a case study in “Divergent” movie - I Gede Krisna Wedhana Cahyadi; I Wayan Dana Ardika; Ni Nyoman Yuliantini (English, 2017)
Maxim is general principle which is thought to underlie the efficient use of language. This research was conducted to find out the existence of the generosity maxim applied by the characters in “Divergent” movie and the factors which caused the characters applying the maxim in their utterances throughout the movie. Data of the research was utterances used in the movie. The data was identified by using theory of maxim[1] to see if it merely applied the maxim of generosity and what factors influenced it use in the data. The data were analyzed by using the theory of politeness maxim proposed by Leech[1] and the statements about factors that influence the application of politeness maxims proposed by Holmes[2]. The result analysis was described descriptively. Documentation and observation methods are applied in collecting the data. The result showed that the application of the generosity maxim existing in “Divergent” movie and the factors influencing the application of the maxim in this movie are gender and context of situation. The factors which most frequently influenced the application of the generosity maxim in the movie is the context of situation, and the factor which least frequently influenced the application of the maxim is gender.